Thermal impact of adhesive-mounted rooftop PV on underlying roof shingles. (1st November 2018) - Shukla, Nitin; Watts, Alliston; Honeker, Christian; Hill, Mark; Kośny, Jan
Highlights: There is concern that adhesive-mounted rooftop PV can raise shingle temperature. Test hut study was conducted in Albuquerque, NM during summer months. No evidence of heat buildup under the PV module was observed. Adhesive-mounted PV caused significant reduction in daily peak roof heat flows. Abstract: Adhesive mounting of residential rooftop photovoltaics (PV) is an alternative to traditional rack mounting that reduces installation costs. Adhesive mounting is fast, simple and reduces the need for skilled labor. In our novel design that further reduces the installation costs, a lightweight (glassless and frameless) PV module is directly adhered to a shingled roof using an adhesive tape, creating a <5 mm air gap between the PV back-panel and the roof shingle surface. Although the gap is sufficient for moisture and rainwater transport under the PV panel, potential heat buildup under the module may adversely impact the long-term durability of the shingles. Heat buildup may also increase the heat flux through the roof, resulting in an overall increase in building cooling loads. This study investigates the thermal behavior of the roof under an adhered PV system. Two identical test huts with dark shingle-covered roofs were located in the hot, desert climate of Albuquerque, NM. Adhesively-mounted lightweight PV modules were installed on the south-facing roof of one of the test huts (PV hut), with the other one serving as a reference hut. During the summer season, the asphalt roof shingles under the PV modules experienced a 13 °C reduction in daytime peak temperature compared with the exposed shingles. No evidence of heat buildup under the PV module was observed. It was also found that the temperature of shingles underneath the adhesive was up to 6 °C higher than for shingles underneath the gap space at the daily peak time. Thin but ventilated air gap between the PV back-panel and the roof shingles helped remove the heat, while the adhesive pads (patches) served as thermal bridges between the PV module and the roof. Daily peak heat flow through the attic ceiling was almost 49% lower in the PV hut compared to the reference hut. These results show no evidence of an adverse thermal impact of the adhesive-mounted PV system on the roofing materials, while demonstrating a potential for a notable reduction in space conditioning energy requirements.